The Routledge handbook of religions and global development (Routledge international handbooks, 2015)
"This handbook provides a cutting-edge survey of the state of research on religions and global development. Part one highlights critical debates that have emerged within research on religions and development, particularly with respect to theoretical, conceptual and methodological considerations, from the perspective of development studies and its associated disciplines. Parts two to six look at different regional and national development contexts and the place of religion within these. These parts integrate and examine the critical debates raised in part one within empirical case studies from a range of religions and regions. Different religions are situated within actual locations and case studies thus allowing a detailed and contextual understanding of their relationships to development to emerge. Part seven examines the links between some important areas within development policy and practice where religion is now being considered, including: faith-based organizations and development; public health, religion and development; human rights, religion and development; global institutions and religious engagement in development; sustainable development, climate change and religion; economic development and religion; religion, development and fragile states; development and faith-based education. Taking a global approach, the handbook covers Africa, Latin America, South Asia, East and South-East Asia and the Middle East. It is essential reading for students and researchers in development studies and religious studies, and is highly relevant to those working in a range of disciplines, from theology, anthropology, and economics, to geography, international relations, politics, sociology, area studies and development studies" --Provided by publisher